Use of climate information in soybean farming on the Argentinean pampas - Bert, Federico Esteban (2007)
The availability of enhanced climate forecasts offers the potential for farmers to improve responses to climate variability. However, few studies have demonstrated actual effective uses of climate forecasts. Through interaction with regional agricultural experts, we evaluated the opportunities and constraints involved in the use of climate information in decision making regarding soybean farming in the Argentinean pampas. Our results showed that opportunities exist for the successful application of climate information, but consistent with previous research, there is a need to consider the broad and complex context influencing decisions, since climate is just one of the many factors affecting farmers' decisions. More importantly, we showed that adaptive management strategies proposed by experts in response to hypothetical climate scenarios produced diverging economic outcomes (both positive and negative). We hypothesized that inconsistency of the observed results could be due to a poor understanding by the agricultural experts of the impacts on regional climate of global climate signals (e.g. a given ENSO phase). An alternative hypothesis was that crop consultants had difficulties in anticipating the agronomic outcomes of management decisions made in response to a given climate forecast. Further research is needed to elucidate to what extent these hypotheses are valid. However, our results suggest that the mere availability of climate forecasts will not necessarily benefit growers. In order for there to be an improvement in the use of seasonal forecasts, appropriate interventions are necessary to enhance decision makers' understanding of the sources and impacts of climate variability, and of the consequences of different responses to a range of climate scenarios.